Thermal ionization of tetramethyltetrazene molecules on NaAuy surface. Issue 5 (October 2020) - Knatko, MV; Lapushkin, MN
Adsorption of tetramethyltetrazene on NaAuy surface leads to formation of aromatic compounds constituting thermal ionization mass spectrum, in accordance with the ionization rules of nitrogen-containing molecules established earlier. The suggested mechanism of tetramethyltetrazene adsorption on NaAuy surface is characteristic of azide adsorption on metal surfaces.